The influence of dissolved organic carbon on primary production in northern lakes - Seekell, David A. (2015)
Dissolved organic carbon (DOC) concentrations in lakes are changing globally, but little is known about potential ecosystem impacts.We evaluated the relationship between DOC and whole-lake primary production in arctic and boreal lakes. Both light extinction (inhibits primary production) and nutrient availability (stimulates primary production) are positively and nonlinearly related to DOC concentration. These nonlinearities create a threshold DOC concentration (4.8 mg/L), below which the DOC-primary production relationship is positive, and above which the relationship is negative. DOC concentration varies maximally between regions, creating a unimodal relationship between primary production and DOC that emerges at broader scales because arctic lakes largely fall below the threshold DOC concentration, but boreal lakes fall above it. Our analysis suggests that the impact of DOC trends on lake primary production will vary across lakes and regions as a result of contrasting baseline conditions relative to the DOC threshold.